Complete resolution of right atrial free-floating thrombus after warfarin therapy in chemotherapy-induced cardiomyopathy: a case report - Mappiare, Mirnawati; Pratiwi, Dian; Muzakkir, Muzakkir (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Free-floating right heart thrombus is a rare phenomenon and has dismal rognosis. The optimal management of free-floating right thrombus remains controversial with no clear consensus. We present a case of right atrial free-floating thrombus in 56-year-old woman in chemotherapy inducedcardiomyopathy. Three weeks of warfarin treatment showed complete thrombus resolution. To the best of our knowledge, no such case has previously been reported in Indonesia.